Real time microwave biochemical sensor based on circular SIW approach for aqueous dielectric detection. - Zakaria, Zahriladha; Md Arshad, Mohd Khairuddin; Awang Md Isa, Azmi; Dasril, Yosza; A. Alahnomi, Rammah; Mohd Bahar, Amyrul Azuan (Nature Research, 2019)
In this study, a critical evaluation of analyte dielectric properties in a microvolume was undertaken, using a microwave biochemical sensor based on a circular substrate integrated waveguide (CSIW) topology. These dielectric properties were numerically investigated based on the resonant perturbation method, as this method provides the best sensing performance as a real-time biochemical detector. To validate these fndings, shifts of the resonant frequency in the presence of aqueous solvents were compared with an ideal permittivity. The sensor prototype required a 2.5µL volume of the liquid sample each time, which still ofered an overall accuracy of better than 99.06%, with an average error measurement of ±0.44%, compared with the commercial and ideal permittivity values. The unloaded Qu factor of the circular substrate-integrated waveguide (CSIW) sensor achieved more than 400 to ensure a precise measurement. At 4.4GHz, a good agreement was observed between simulated and measured results within a broad frequency range, from 1 to 6GHz. The proposed sensor, therefore, ofers high sensitivity detection, a simple structural design, a fast-sensing response, and cost-efectiveness. The proposed sensor in this study will facilitate real improvements in any material characterization applications such as pharmaceutical, bio-sensing, and food processing applications